CULTURE AND TRADITIONS OF ENGLAND (Лучшие интеллектуальные исследования, 2025)
Annotation: This article explores the rich culture and traditions of England, including national holidays, literature, art, music, food, and social customs. It highlights the historical roots of English cultural identity and how traditional practices continue to shape modern life in England. The article is intended for learners and researchers interested in British culture and its influence on global society.Annotatsiya: Ushbu maqolada Angliyaning boy madaniyati va an’analari – milliy bayramlar, adabiyot, san’at, musiqa, taomlar hamda ijtimoiy urf-odatlar haqida so‘z yuritiladi. Unda ingliz madaniyatining tarixiy ildizlari va zamonaviy hayotdagi o‘rni yoritib beriladi. Maqola ingliz madaniyatini o‘rganayotgan o‘quvchilar va tadqiqotchilar uchun mo‘ljallangan.